The characteristic of endothelium-dependent vasodilatation in athletes and untrained volunteers - V. V. Kologrivova; A. N. Zakharova; E. V. Pakhomova; V. N. Vasilyev; L. V. Kapilevich (Бюллетень сибирской медицины)
It is shown that strength-training athletes and track and field athletes have endothelial dysfunction. The vascular endothelium activity is not related to the direction of physical exercises. At the same time, the dynamic physical exercise induces endothelium vasodilatation function in all groups. Apparently, it can be the adaptive response to regular high-intensity physical exercises. At the same time it is a risk factor for acute vascular disorders.